Social organization of the Bedouin tribe systems - Adaim, Ali H. (Al-Adab Journal, 2015)
The nomad communities are regarded as one of the oldest human communities that preceded all other communities. These communities are characterized by their simplicity and the few of its population, the research included the following points:Introduction: which includes a summary of the nature of the nomad communities, the traditions and social costumes they practice and the features they have, in addition to the structural places which they possess.The General framework of the Study includes the problem and importance of the study:The concepts followed by the nomad community:The meaning of nomadThe meaning of BedouinThe Bedouin characterThe nature of tribal social organization:The composition of tribal organizationThe kinship systemMarriage system ‘the means of social disciplinethe prevalent activities in the nomad communitiesMethod of livingThe economic activities which includesHerdingAnimal cultivationNew activities6. Findings and recommend